NILAI BUDAYA DASAR TOKOH UTAMA DALAM NOVEL ANTARA IBUKU & IBUKU KARYA DESNI INTAN SURI - Yulia Sisri; Bakhtaruddin Nasution; Hamidin Hamidin (Jurnal Bahasa dan Sastra, 2013)
The purpose of this article is to describe the basic cultural values ​​that include love, beauty, suffering, justice, philosophy of life, responsibility, anxiety, and expectations are shown the main character in the novel Antara Ibuku & Ibuku written by Desni Intan Suri. This research data in the form of sentences, either in the form of dialogue, monologue, or narrative related to basic cultural values ​​contained in the novel Antara Ibuku & Ibuku written by Desni Intan Suri. Data sources of this study is novel Antara Ibuku & Ibuku written by Desni Intan Suri. findings of the study are (1) man and love, such as love of God, the family, and to others, (2) human and beauty, such as objective and subjective beauty, (3) human and suffering, such as pain and torment; (4) human and justice, is a form of legal or moral justice; (5) and the human way of life, in the form of virtue and principle of life, (6) human and responsibilities, such as responsibility towards god and yourself; (7) human and anxiety, such as restlessness, anxiety, uncertainty and fear, and (8) of human and expectations.